2020
DOI: 10.1038/s41598-020-64182-2
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping kura clover with prairie cordgrass mitigates soil greenhouse gas fluxes

Abstract: Prairie cordgrass (PCG) (Spartina pectinata Link) has a high tolerance to soil salinity and waterlogging, therefore, it can thrive on marginal lands. Optimizing the nitrogen (N) input is crucial to achieving desirable biomass production of PCG without negatively impacting the environment. Thus, this study was based on the hypothesis that the use of legumes such as kura clover (Trifolium ambiguum M. Bieb.) (KC) as an intercrop with PCG can provide extra N to the crop reducing the additional N fertilizer and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…The composition of triglycerides with C16-C18 corresponds to the hydrocarbon structure of diesel. Thus, Jatropha oil could be used directly as diesel as a road transportation fuel without further processing [128]. Generally, standard biodiesel and J. curcas oil compare well to petroleum-based diesel [5].…”
Section: Composition Of J Curcas Oilmentioning
confidence: 99%
“…The composition of triglycerides with C16-C18 corresponds to the hydrocarbon structure of diesel. Thus, Jatropha oil could be used directly as diesel as a road transportation fuel without further processing [128]. Generally, standard biodiesel and J. curcas oil compare well to petroleum-based diesel [5].…”
Section: Composition Of J Curcas Oilmentioning
confidence: 99%
“…Biochar and manure have been documented to be effective in reducing CH 4 flux from waterlogged soils, the largest source of global CH 4 flux (Feng et al, 2012;Khan et al, 2013;Kim et al, 2014). Dry cropping systems have been found to emit inconsiderable amounts of CH 4 in previous research (Abagandura et al, 2020;Bhattarai et al, 2021;Singh et al, 2020).…”
Section: Ghg Fluxes and Global Warming Potentialmentioning
confidence: 99%
“…Several studies have reported the benefits of PCG-KC intercropping (Abagandura et al, 2020;Kim et al, 2020;Sekaran et al, 2020). For example, a previous study in South Dakota by Sekaran et al (2020) reported that PCG-KC intercropping enhances soil microbial communities when compared to the PCG monocultures fertilized with different levels of N in a silty clay loam soil type.…”
mentioning
confidence: 99%
“…However, this experiment was conducted only after crop harvest, and there is a lack of understanding of changes in the biological properties during the crop growth period. In another study conducted on a silty clay loam soil type, Abagandura et al (2020) reported that after 7 years of intercropping, PCG-KC enhances soil organic carbon (SOC), total nitrogen (TN), and different soil C and N fractions such as cold and hot water extractable C and N and microbial biomass C and N in the topsoil (0-to 15-cm soil depth)…”
mentioning
confidence: 99%